View of the High Market (Hoher Markt), the town hall (Rathaus), and the Wedding Fountain (Vermählungsbrunnen), in Vienna - Sigrist, Johann, 1756-1807 (engraver):::Creator::::::::::::; Fischer von Erlach, Joseph Emanuel, 1693-1742 (artist):::Contributor:::::::::::: (Augsburg; Academie Imperiale d'Empire des Arts libereaux; Germany)
Color vue d'optique of the Hoher Markt in Vienna, showing the Rathaus and the Vermählungsbrunnen; intended for viewing through an optical machine such as a zograscope or peep box with a curved lens and mirror that makes the print appear to be three-dimensional.